Novel giant magnetostrictive material current sensor. Issue 1 (June 2015) - Shen, Yan; Liu, Zhao; Lin, Qiuyan; Ge, Jinming; Zhang, Guoqing; Yu, Wenbin
Abstract: Because of the shortcomings of the traditional inductive current sensor and optical current sensor, this paper proposes a new type of current sensor that uses a giant magnetostrictive material (GMM) to monitor and control power lines. This paper introduces operating principle and structure design of a GMM current sensor. To eliminate the frequency- doubled effect and to obtain good linearity, we set the bias magnetic field to 11.53 kA/m and the prestress force to 6 MPa. The strains of the 100- and 200-mm GMM sticks under the same magnetic field were compared; the results showed that the 100-mm stick had a larger strain. The magnetic field interference during a single-phase measurement of power lines was also studied. Finally, we analyzed the device sensitivity and discussed its influencing factors. The sensitivity reached 4 × 10 -9 m 2 /A.